The practical pumping handbook - Mackay, Ross (Elsevier, 2004)
This book is a practical account of pumping, piping and seals starting with basics and providing detailed but accessible information on all aspects of the pumping process and what can go wrong with it. Written by an acknowledged expert with years of teaching experience in the practical understanding of pumps and systems. Aids understanding of pumps to minimize failures and time-out. A practical handbook covering the basics of the pumping process. Written by an acknowledged expert.